Enhancing Zakat Fundraising through Digital Financial Transparency: Evidence from Indonesian Amil Zakat Institutions - Haris, Abdul (Journal of Management and Business, 2025)
This study aims to analyze the relationship between the level of transparency of financial statements of amil zakat institutions (LAZ) and the effectiveness of collecting zakat, infaq, and alms (ZIS) funds. In the midst of an increase in the potential for national zakat which reached Rp 327 trillion, the realization of fundraising is still far from optimal, only around 10% per year. One of the main factors causing this is the low level of disclosure of financial statements by LAZ, especially at the district/city level which only reaches 12% of public exposure. This study uses a qualitative and quantitative descriptive approach, through the analysis of 18 LAZ financial documents available online. Ratio analysis techniques were used to measure efficiency (ACR), speed of fund distribution (ZIS Turn Over), operational efficiency (Amil Portion), and zakat growth (ZIS Growth), while K-Means, Silhouette Score, and Inertia clustering techniques were used to identify performance patterns between institutions. The results of the study show that institutions that consistently report finances openly have more stable and efficient financial performance than institutions that are not transparent. Clustering shows three main performance patterns: efficient and growing institutions, fluctuating institutions with high risk, and stagnant institutions with low potential. This research confirms that transparency is not only an administrative need, but is a strategic instrument in strengthening social legitimacy, increasing public trust, and optimizing the collection of ZIS funds. Therefore, digital-based financial reporting governance reform and social values are an important agenda in strengthening zakat institutions in Indonesia.